2018
DOI: 10.1186/s13104-018-3578-0
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent deliveries in urban Cameroon: a retrospective analysis of the prevalence, 6-year trend and adverse outcomes

Abstract: ObjectiveAdolescent deliveries remain a public health problem in most developing countries. The aim of our study was to determine the prevalence, trends and outcome of adolescent deliveries in an urban setting in Cameroon. We carried out a retrospective register analysis over a 6-year period (January 2010–December 2015) at the Saint Albert Le Grand hospital Douala.ResultsThe overall prevalence of adolescent deliveries was 8.2% (662 out of 8056). There was a significant decrease over the 6-year period (p-trend:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…Two of the studies reported on the same cohort of womenone reporting on birth outcomes in women and the other on birth outcomes in the children [6,13]. Two studies provided estimates for the prevalence of adolescent deliveries in the North west region [1,2], two studies provided estimates for the South west region [3,17], two studies for the Centre region [6,7,13], one for the Littoral region [9], one for the Far north region [10] and one study provided an estimate from all ten regions in the country [12]. All the studies used to assess the prevalence of adolescent deliveries were cross-sectional studies but Egbe et al used a case-control design in the second phase of their study to determine the maternal and foetal outcomes of adolescent deliveries [17].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two of the studies reported on the same cohort of womenone reporting on birth outcomes in women and the other on birth outcomes in the children [6,13]. Two studies provided estimates for the prevalence of adolescent deliveries in the North west region [1,2], two studies provided estimates for the South west region [3,17], two studies for the Centre region [6,7,13], one for the Littoral region [9], one for the Far north region [10] and one study provided an estimate from all ten regions in the country [12]. All the studies used to assess the prevalence of adolescent deliveries were cross-sectional studies but Egbe et al used a case-control design in the second phase of their study to determine the maternal and foetal outcomes of adolescent deliveries [17].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the estimates for the various regions. Four studies reported on the prevalence of early and late adolescent deliveries [1,3,9,10]. The overall pooled estimate for early adolescent deliveries was 2.8% (95% CI: 0.4-7.2%, I 2 = 99.6%, χ 2 = 812.7, p < 0.001), meanwhile that for late adolescent deliveries was 12.5% (95% CI: 6.7-19.8%, I 2 = 99.6%, χ 2 = 747.5, p < 0.001) (Additional File 5).…”
Section: Prevalence Of Adolescent Deliveriesmentioning
confidence: 99%
See 3 more Smart Citations